2014
DOI: 10.1007/s11356-014-3705-y
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid alkali-hydrodynamic disintegration of waste-activated sludge before two-stage anaerobic digestion process

Abstract: The first step of anaerobic digestion, the hydrolysis, is regarded as the rate-limiting step in the degradation of complex organic compounds, such as waste-activated sludge (WAS). The aim of lab-scale experiments was to pre-hydrolyze the sludge by means of low intensive alkaline sludge conditioning before applying hydrodynamic disintegration, as the pre-treatment procedure. Application of both processes as a hybrid disintegration sludge technology resulted in a higher organic matter release (soluble chemical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…containing undetectable levels of pathogens, can be used for agricultural purposes. However, 75% of the stabilized sewage sludge used for agriculture belonged to Class B biosolids with pathogens (Grübel and Suschka, 2015). For Class A biosolids, of the level of fecal coliforms as an indicator of pathogen should be strictly monitored, while the monitoring of enteric viruses, helminth ova, and Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…containing undetectable levels of pathogens, can be used for agricultural purposes. However, 75% of the stabilized sewage sludge used for agriculture belonged to Class B biosolids with pathogens (Grübel and Suschka, 2015). For Class A biosolids, of the level of fecal coliforms as an indicator of pathogen should be strictly monitored, while the monitoring of enteric viruses, helminth ova, and Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…The Grübel & Suschka () reported that after two stages of anaerobic digestion (mesophilic and thermophilic anaerobic digestion), the highest TS reduction amounted to 45.6% (Grübel & Suschka ). Kavitha et al .…”
Section: Resultsmentioning
confidence: 99%
“…The Gr€ ubel & Suschka (2015) reported that after two stages of anaerobic digestion (mesophilic and thermophilic anaerobic digestion), the highest TS reduction amounted to 45.6% (Gr€ ubel & Suschka 2015). Kavitha et al (2016) investigated the effect of combined surfactant-dispersion pretreatment on dairy waste activated sludge) reduction in anaerobic digesters.…”
Section: Semi-continuous Operation Of Thermophilic Anaerobic Digestionmentioning
confidence: 99%
“…In recent years, several pre-treatment / disintegration methods have been applied both on a bench and technical scale, for example by using thermal energy [23,24], enzymes [25], ozonisation [26], acidification [27], alkalization [28,29], high pressure [30,31], mechanical grinding [32] and ultrasound energy [33,34]. In general, these techniques can be split into 3 categories: biological, physical and chemical (Fig.…”
Section: Pre-treatment Methodsmentioning
confidence: 99%